Sleeping dogs [compact disc, unabridged] : a novel - Perry, Thomas, 1947- (Perry, Thomas, 1947- Butcher's Boy, 2009)
A tour-de-force novel of suspense by the Edgar-winning author of The Butcher's Boy. He came to England to rest. He used to be the Butcher's Boy, the highly skilled mob hit man. Now, after a decade, they've found him. The Butcher's Boy escapes back to the States with more reasons to kill. Until the odds turn terrifyingly against him.